Pengaruh Pemberdayaan Perempuan Terhadap Pelayanan Kebidanan: Literature Review - Izzatul Ainiyah; Dwi Izzati Budiono (Oksitosin : Jurnal Ilmiah Kebidanan, 2022)
One of Sustainable Developement Goal by United Nations is to achieve gender equality and empowering women. Women empowerment in health field is also one of the most effective strategy to achieve this goal as well as other goals related to this issue. Midwife as a profession act as women partner and have a philosophy that every women needs tobe empowered. This study aim to review some literature about the effect of women empowerment in midwifery services. This study was a secondary research in form of literature review from articles we had collected from Pubmed dan Science direct. There are total of 21 literatures that fit inclusion and exclusion criterias set by researcher. Based on this review, women empowerment in midwifery services increased maternal and child health, but however it might caused an unexpected negative effect such as increased medicalisation of childbirth which could harm women. Further primary research required to validate these data.